Portulaca oleracea L.: genotypes phenology and thermal sum in tropical climate - Correa, Amanda Ribeiro; Arantes, Cárita Rodrigues de Aquino; Camili, Elisangela Clarete; Guimarães, Sebastião Carneiro (Revista em Agronegócio e Meio Ambiente, 2023)
Portulaca oleracea L., known as purslane, is an unconventional food plant rich in nutrients and medicinal properties, with potential for consumption and commercialization. The objective was to describe phenological stages of purslane based on BBCH (Biologische Bundesantalt, Bundessortenamt and Chemische Industrie) scale and thermal sum at different times. Evaluations were made from two genotypes, the Golden variety and an access. Plants were observed during six consecutive periods, interspersed every two months. Thermal sum and base temperature were obtained considering the average temperature from seedling emergence to flowering and dispersion of the first capsule in 50% of the plants. The phenological cycle of Purslane based on the BBCH scale shows seven main stages, subdivided into secondary stages: germination (0); leaf development on the main branch (1); development of lateral branches (2); development of flower buds (5); flowering (6); seed dispersal (8); and senescence (9). The lower base temperatures (Tb) determined to flowering were 10 to 15 ºC for the variety Golden and access, respectively, since for seed dispersal, Tb was 9 and 13 ºC, respectively. Thermal requirements for Golden variety are 421.3 GD for flowering and 644.2 GD for seed dispersal, while for access they are 239.7 and 407.0 GD, respectively. Purslane as a food plant can be produced throughout the year in tropical region and may be best used if harvested until the plants reach 12 or 10 leaves.